Intranasal delivery of lipid-based nanosystems as a promising approach for brain targeting of the new-generation antiepileptic drug perampanel - Meirinho, Sara (2023)
Perampanel (PER), a new-generation antiepileptic drug effective against different types of seizures, has already demonstrated a potential in status epilepticus therapy. Considering the growing interest of intranasal (IN) administration for nose-to-brain delivery, PER could be envisioned as a good candidate for this route, especially if formulated in a lipid-based nanosystem. With that purpose, a hydrophobic formulation (FO1.2) and a self-microemulsifying drug delivery system (SMEDDS) (FH5) loaded with PER were developed and characterized. Following PER IN administration (1 mg/kg) to mice, its pharmacokinetics was characterized and compared with intravenous and oral routes. Histopathological toxicity was also examined after a 7-day repeated dose study. FH5 homogeneously formed nanodroplets upon dispersion (20.07 ± 0.03 nm), showing a sustained in vitro PER release profile up to 4 h. By IN route, PER brain delivery was more extensive with FH5 (Cmax and AUC of 52.32 ng/g and 190.35 ng.h/g for FO1.2; 93.87 ng/g and 257.75 ng.h/g for FH5). Maximum brain concentration and total brain exposure were higher than those obtained after oral dosage, with maximum PER concentrations reached significantly faster than post-oral administration (15 min vs 2 h). An improvement in PER plasmatic concentration was also obtained, demonstrated by high relative bioavailability values (134.1% for FH5 and 107.8% for FO1.2). PER absolute plasma bioavailability after IN delivery was 55.5% for FH5 and 44.6% for FO1.2, ensuring a somewhat improved targeting of PER to the brain by the IN route compared to the IV route. No signs of toxicity were found by histopathologic evaluation. Results suggest that IN administration of PER might be a feasible and safe approach for acute and chronic epilepsy management, especially using delivery systems as SMEDDS.